PENGEMBANGAN MODUL MATA KULIAH GAMBAR TEKNIK SEBAGAI UPAYA UNTUK MENINGKATKAN PRESTASI MAHASISWA PADA JURUSAN TEKNIK MESIN D3 IST AKPRIND YOGYAKARTA - Aji Pranoto (Jurnal Pendidikan Vokasi Otomotif, 2019)
This research aim to: (1) know the module development process, (2) to know the feasibility and (3) find out the effectiveness of the module to interpret engineering drawings, which have been made to support learning in interpret engineering drawings subject. The method that used in this research is research and development methods. Collection data was done by using questionnaires and test questions. The techniques of data analysis was done by using descriptive analysis techniques, by analyzing quantitative data and then interpreted in a qualitative sense. The results showed that: (1) learning module development process carried out in four main stages: needs analyze, design and creating a module, testing the feasibility and effectiveness of testing modules, (2) feasibility testing shows an average percentage value 88% with "very good" criteria and can concluded the learning interpret engineering drawings module is feasible to used for the learning process, and (3) the effectiveness testing is done by comparing the posttest experimental class value with the posttest class control value,obtained the t count value = 3.701 with the conclusion that the using of developed modules can effectively used to support learning in interpret engineering drawings subject.